Level of Knowledge About Attention-Deficit/Hyperactivity Disorder (ADHD) Among Medical Interns - Vásquez-López, Alexia N. (2025)
Objective: To determine the level of knowledge among medical interns regarding Attention-Deficit/Hyperactivity Disorder (ADHD), among students of a local university. Methodology: A cross-sectional observational study was conducted with a population (n = 1.050) consisting of medical interns rotating in healthcare centers in Metropolitan Lima. A non-probabilistic convenience sample (n = 281) was selected. Results: The analysis revealed that 83.6 % of the studied sample of medical interns had a good knowledge about the signs and characteristics of ADHD, while the remaining 16.4% presented poor knowledge levels. Conclusions: Most participants in this study were familiar with the diagnostic criteria of ADHD set out in the DSM-V, although there is a significant percentage who required further training to adequately identify the distinctive signs of the disorder.